Pengaruh Pemberian Infusa Albedo Semangka terhadap Perubahan Ukuran Diameter Pulau Langerhans Pankreas Tikus Jantan (Rattus norvegicus) Diabetes Mellitus - Widi Pangestu Wilujeng; Nurul Mahmudati; Ladiya Fitri Ma’rufah; Ninik Fadhillah; Fatmi Indah Hati; Gebby Agnessya Esa Oktavia; Aurira Thrisna Dwi Aprianti; Berlian Rustantina; Nazil Dwi Rahayuningtyas; Azizaturrohmah; Farah Annisa Nurbani; Hanik Faizah; Alfiah Hayati (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Diabetes Mellitus condition (DM) correlates with the damage that occur in pancreas especially in Langerhans islets, one of the damage indicators is diameter changes of Langerhans islets that getting smaller compare with the normal sizes. The use of natural ingredients to control diabetes mellitus can be done by infusing sweet beauty watermelon albedo which can be found abundant in traditional market. Albedo layer of watermelon contain antioxidant compounds that can help to regenerate Langerhans islets of pancreas. This study purpose was to know the effect of giving watermelon’s infusion albedo to diameter of Langerhans islets in diabetes mellitus rats (Rattus norvegicus), and analyze the potential process occurred based on the result as information source for other research. This study used 25 male rats (Rattus norvegicus) as animal model with 5 groups treatment which were normal group, positive group as control (DM without treatment), A group (DM+1000 mg/kgBB watermelon’s infusions albedo), B group (DM+1500 mg/kgBB watermelon’s infusions albedo), and C group (DM+2000 mg/kgBB watermelon’s infusions albedo). After all the treatments, the rats were anesthetized and dissected and then their pancreas was taken. The pancreas was processed into histological slides by fixing the pancreas in a fixative solution (10% formalin) then dehydrated in a series of graded ethanol and embedded in paraffin wax, cut at a thickness of 4 µm, and finally stained with hematoxylin-eosin dye for microscopic observation, according to the stages Histopathological analysis of the gonads was examined using standard methods. Data was collected by measuring the size of Langerhans islets with microscope Olympus CX33 and connected to the raster image application. Data results from this study indicate that watermelon’s infusion albedo had effect to increase the diameter of Langerhans islets of rat with diabetes mellitus